PENGARUH TERAPI MUSIK PANTING TERHADAP KECEMASAN PASIEN DI RUANG ICCU RSUD ULIN BANJARMASIN - Setyawan, Imam; Nasution, Tina Handayani; Pertiwiwati, Endang; Hafifah, Ifa (Coping: Community of Publishing in Nursing; Vol 11 No 2 (2023): April 2023DO - 10.24843/coping.2023.v11.i02.p10, 2023)
ICCU patients often experience psychiatric problems, one of which is anxiety. Anxiety in ICCU patients results in changes in coping patterns for their heart disease. One effort to reduce anxiety is important music therapy which can provide a relaxing effect. The research objective was to determine the effect of panting music therapy on patient anxiety in the ICCU room at Ulin Hospital, Banjarmasin. This research is a quantitative type of quasiexperimental method with a one-group pre-posttest design. The research sample was 30 ICCU patients who were selected using a non-probability technique, namely consecutive sampling. The effect of panting music therapy on patient anxiety was analyzed using the Wilcoxon test. The results showed that in the pre-test the majority of respondents experienced mild anxiety, 18 (60%) people and the results of the post-test, the majority of respondents did not experience anxiety, 15 (50%) people. The Wilcoxon test showed p-value of 0,000 with an error rate of 5%. The conclusion in this study is that there is an effect of panting music therapy on patient anxiety in the ICCU room at Ulin Hospital, Banjarmasin. Panting music therapy has a slow rhythm that produces a feeling of relaxation and reduces symptoms in patients experiencing anxiety.